2014
DOI: 10.3758/s13414-014-0748-6
|View full text |Cite
|
Sign up to set email alerts
|

The projected hand illusion: component structure in a community sample and association with demographics, cognition, and psychotic-like experiences

Abstract: The projected hand illusion (PHI) is a variant of the rubber hand illusion (RHI), and both are commonly used to study mechanisms of self-perception. A questionnaire was developed by Longo et al. (2008) to measure qualitative changes in the RHI. Such psychometric analyses have not yet been conducted on the questionnaire for the PHI. The present study is an attempt to validate minor modifications of the questionnaire of Longo et al. to assess the PHI in a community sample (n = 48) and to determine the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 61 publications
6
51
4
Order By: Relevance
“…For example, embodiment of the “other” hand is proportionally related to disembodiment of one’s real hand, with the total embodiment of both being equal to one single hand (44, 45). A similar balance also exists with the sense of agency (46). Disembodiment (of limbs) and reduced agency (over actions) are clinical features of persons with passivity symptoms, so performance on such measures are of particular interest.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…For example, embodiment of the “other” hand is proportionally related to disembodiment of one’s real hand, with the total embodiment of both being equal to one single hand (44, 45). A similar balance also exists with the sense of agency (46). Disembodiment (of limbs) and reduced agency (over actions) are clinical features of persons with passivity symptoms, so performance on such measures are of particular interest.…”
Section: Introductionmentioning
confidence: 70%
“…Participant were exposed to each condition once (3 min each), with the order of presentation being counter-balanced across participants. A 20-item questionnaire assessing the subjective experience of the illusion was administered after each condition (46); adapted from Ref. (43).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These restrictions can be overcome by using a live video image of the participant’s hand. In the video-version of the RHI (the “projected hand illusion (PHI)”; Graham et al, 2015), the rubber hand is replaced by a live video image of the participant’s own hand. As well as allowing precise manipulation of the synchrony of seen and felt brush strokes, the PHI allows the congruency between seen and felt movements to be manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…In the PHI, an unmanipulated video image of the participant’s hand is typically either projected onto the surface of a table (e.g., Tsakiris et al, 2006) or shown via a display screen embedded within a table (e.g., Graham et al, 2015). A disadvantage of this set-up is that the viewed hand is in a different plane to the real hand, which may require additional computation factors for the brain to overcome.…”
Section: Introductionmentioning
confidence: 99%